Knowledge and practices of toothbrushing among first-year odonto-stomatology students in Vietnam - Linh Dieu Thi Bui; Lam Nguyen Le; Ngan Bich Thi Truong; Ngan Kim Thi Huynh; Nhi Phuong Nguyen Van; Trieu Minh Bui; Trinh Diem Thi Huynh (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: The hypothesis suggests that first-year odonto-stomatology students are young and have limited knowledge and experience in their field and do not fully understand the significance and importance of oral health care. Moreover, they are a key focus for future development, as odonto-stomatology students should serve as positive role models for oral health attitudes and behaviors toward their families, patients, and peers. First-year odonto-stomatology students play a crucial role in building a foundation of knowledge and skills for the future, serving as practitioners and advocates for proper oral hygiene practices. Purpose: The aim is to determine toothbrush knowledge and practices among first-year students of the Odonto-Stomatology Faculty regarding specific aspects: the number of times to brush teeth per day, tooth brushing duration, the types of tooth brushing techniques, tooth brushing timings, toothbrush replacement frequency, and oral hygiene tools. These aspects are compared with the standards of other studies worldwide conducted within the last ten years. Methods: This study followed a descriptive, analytical, cross-sectional method. All first-year students of the Odonto-Stomatology Faculty agreed to participate in the study, except for those meeting the exclusion criteria. The data were collected through a survey questionnaire administered via Google Forms and analyzed using SPSS software. Results: In this study, 185 first-year students of the Odonto-Stomatology Faculty were eligible to participate. Most students had differences in knowledge and practice about brushing their teeth, including the number of times they brush their teeth per day, brushing technique, brushing time, toothbrush changing time, and how to use oral hygiene tools. These differences were statistically significant, with p < 0.001. More than 90% of the students reported that they brush their teeth two to three times per day, using a regular toothbrush and toothpaste. The percentage of students who brushed their teeth two to three times per day and used toothbrushes with toothpaste was the highest (91.4%). Conclusion: Most students have more knowledge and practice compared with other studies in the literature. The majority of students have decent knowledge and good practices of toothbrushing, but there are still some students who do not.